FAKTOR-FAKTOR YANG MEMPENGARUHI PERUBAHAN HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFT AR DI BURSA EFEK INDONESIA PERIODE 2008-2009 - Saragih, Joana L (Jurnal Manajemen dan Bisnis, 2010)
This purpose of research is aim to know and proves empirically about monetary performance inï¬‚uence to stock price change at banking company in Indonesia Stock Exchange. Research beneï¬t is add knowledge and knowledge of writer about monetary performance inï¬‚uence to stock price change. Population of Research is all listing banking company of Eï¬‚k Indonesia 26 banks the year 2008-2009. Research sample is all member of population. Data applied is secondary data collected through documentation technique. Data analytical technique applied is doubled linear regression. From result of research is obtained by equation of doubled linear regression is Y = - 394,031 + 93,838X1 - 369,665X2 + 86,279X3 + 449,883X4 - 22,348X5 + 3,072X6. Mean, capital adequancy ratio, net margin interest, return asset on, and net proï¬t margin inï¬‚uential positive to stock price change at banking company. While return on risked asset and loan to deposit ratio inï¬‚uential negativity to stock price change at banking company. Result of test result F, indicates that capital adequancy ratio, retum on risked asset, net margin interest, return asset on, loan to deposit ratio and net proï¬t margin inï¬‚uential positive and signiï¬kan in sirrzultan to stock price change at Perusahaan Perbankan in Indonesia Stock Exchange. Result of test result t, indicates that capital adequancy ratio, return on risked asset, net margin interest, return asset on, loan to deposit ratio and net proï¬t margin inï¬‚uential signiï¬kan parsially to stock price change at Perusahaan Perbankan in Indonesia Stock Exchange. Correlation coeï¬‚icient value ( R) 0,761. Mean, capital adequancy ratio, return on risked asset, net margin interest, return asset on, loan to deposit ratio and net proï¬t margin to stock price change. Determinant coeï¬icient value ( R Square) 0,580. Mean, explainable stock price change by capital adequancy ratio, return on risked asset, net margin interest, return asset on, loan to deposit ratio and net proï¬t margin equal to 58%, while 42% again explained by other factor. In simultan monetary performance variable had an effect on positive to stock price change, while parsially monetary performance had an ejfect on negative and positive to stock price change. Suggestion given to researcher hereinafter is be better if researcher hereinafter adds company becoming research sample.